Analyzing eWOM Dimensions on TikTok and Its Impact on First-Time Voters in the 2024 Presidential Election: A Confirmatory Factor Analysis - Fathimatuz, Zahra; Iskamto, Dedi; Trianasari, Nurvita (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
This paper seeks to examine the dimensions of electric word of mouth (eWOM), namely information quality, information quantity, information credibility, information task-fit, needs of information, and attitude towards information in terms of political marketing. The survey was distributed to 30 respondents who are first-time voters in the 2024 presidential election and seek information on TikTok. It can be concluded that electronic word of mouth through TikTok application affects first-time voters’ decision in Presidential Election 2024 through some dimensions. Various studies have compared the effectiveness of eWOM communication, but research on eWOM in the context of political marketing remains limited. The rise of technology has introduced new campaign strategies, such as those on TikTok, making it essential to understand how eWOM influences voting decisions, particularly among first-time voters.